2014
DOI: 10.2176/nmc.cr2012-0220
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Superficial Sylvian Vein Thrombosis With Long Cord Sign: Case Report and Review of the Literature

Abstract: Isolated cortical vein thrombosis (ICVT) is extremely rare. Only single case or small series of ICVT have been reported; clinical details are still uncertain. We report a case of isolated superficial sylvian vein thrombosis with exceedingly long cord sign. A 14-year-old female with severe sudden onset headache visited our hospital. Fluid attenuated inversion recovery and echo-planar T 2 * susceptibility-weighted imaging (T 2 *SW) showed a long cord sign on the surface of the sylvian fissure. The patency of dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 32 publications
(37 reference statements)
1
17
0
Order By: Relevance
“…The youngest ICVT cases reported previously occurred in two 14-yearold patients. 20,43 There was a female predominance in this case series, which is also consistent with previously published data. 22,23 Patients with ICVT may present with a variety of symptoms, including focal or generalized seizures, headaches, hemiparesis, sensory disturbances, and other focal deficits, often without signs of elevated intracranial pressure.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The youngest ICVT cases reported previously occurred in two 14-yearold patients. 20,43 There was a female predominance in this case series, which is also consistent with previously published data. 22,23 Patients with ICVT may present with a variety of symptoms, including focal or generalized seizures, headaches, hemiparesis, sensory disturbances, and other focal deficits, often without signs of elevated intracranial pressure.…”
Section: Discussionsupporting
confidence: 92%
“…A recent review also concluded that MRV results are neither objective nor definitive, and their role in ICVT diagnosis is either supportive or useless. 20 In this case series, MRV was most useful in confirming the patency of the venous sinuses and deep cerebral veins and determining recanalization of the ICVT at follow-up.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…ICVT is a rare and poorly understood condition that has only been documented in case reports or case series (116 total patients studied in a comprehensive 2014 review of the literature)1 and represents less than 0.063% of all cerebral strokes 2. It frequently involves anastomotic surface vessels such as the vein of Trolard, the vein of Labbé, the superficial Sylvian vein and the precentral, postcentral and central veins.…”
Section: Discussionmentioning
confidence: 99%
“…In patients presenting with ICVT as a solitary diagnosis, the mortality rate is 0%; with good outcome 1. While most patients who are diagnosed with ICVT receive anticoagulation and it is considered the standard of care, outcomes may not be different between patients who receive anticoagulation and those who do not 2…”
Section: Discussionmentioning
confidence: 99%